IMPLEMENTASI DOUBLE EXPONENTIAL SMOOTHING DENGAN PARAMATETER DAMPED PADA ESTIMASI WISATAWAN TAPANULI SELATAN - Matondang, Silvia Elastari; Lestari, Siska; Hasibuan, Amanda Hapsari Intan; Hasibuan, Lutfiah Syava Azzahra (INTELEKTIUM, 2024)
Indonesia is known as a country with many natural and man-made tourist destinations, especially the South Tapanuli region which has marine, natural and man-made tourist destinations that are attractive and worth visiting for domestic and foreign tourists. In 2023, the number of tourists visiting South Tapanuli will be 422,688 people. This research aims to estimate or predict the number of tourists visiting South Tapanuli in the next 6 years using the Double Exponential Smoothing (DES) method with amortized parameters. Double exponential smoothing (DES) is a forecasting method by predicting time series data with a trend model. To overcome overprediction, an attenuating parameter is added which can reduce the estimated value exponentially. This research also aims to compare the estimated number of tourists in South Tapanuli Regency using the T test. This research shows that the estimated number of tourists coming to South Tapanuli Regency in the next six years will increase. For the t test carried out, the results obtained were tcount < ttable (2.014 < 2.015).